Mobile interaction based on eye movement - A. Maheshwari, K; Radhika, G; Abirami, K (International Journal of Engineering and Technology, 2018)
In the looking for hithertio-unused strategies by which clients and PCs can convey, we explore the value of eye developments as a quick and helpful correspondence mode. As cell phones develop analysts are examining new strategies to facilitate the human-portable cooperation. The obstruction to misusing this medium has not been eye-following innovation but rather the investigation of cooperation methods that join eye developments into the client PC exchange in a characteristic and unpretentious way. This paper discusses some of the human factors and the possible technical considerations that can arise by using eye movement as input medium.Â Â